A roadmap for reducing construction waste for developing countries - Anac, Merve; Gumusburun Ayalp, Gulden; Karabeyeser Bakan, Merve (Mdpi)
With the rapid development of the construction industry, construction waste (CW) has recently attracted much attention in many developing countries such as T & uuml;rkiye. As a result, the effective management of construction waste has emerged as a critical concern at the global level. Reducing and managing CW is imperative to promote sustainable urban development. Although several scholars have made many valuable attempts to develop strategies to minimize CW, one of the most effective ways is to propose a road map for CW minimization, which is a method that has never been applied before, neither in this domain nor in the construction management and architectural domain. Unlike former studies, a roadmap was developed for reducing CW in this study. To create a roadmap, three steps were followed in this study. Firstly, CW causes were identified with a systematic literature review. Then, surveys were conducted with the construction stakeholders to obtain their perceptions of these causes. A normalized mean value analysis was conducted, and the importance and criticality of the CW causes were determined. Secondly, a timeline was developed, and it overlapped with the importance of the causes. Finally, roadmap strategies were created, and solutions were proposed to solve the causes of CW in the short, medium, and long term. The roadmap method, which is often used to develop new technologies, has not been used in this way to solve a problem before. Therefore, the study is unique and offers strategies that can be integrated into other studies.
Keywords: construction waste; road mapping; construction waste management; normalized mean value (NMV) analysis